Sociocultural competence of students of the spanish language in primary school - Pajić, Sonja N. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Sociocutural competence, which is an important aspect of learning Spanish as a foreign language, is analysed in the paper. The aim of the survey is to point at this phenomena trough examination of the sociocultural competence of students of the Spanish language in a primary school. The sample survey included students of the eighth grade of the primary school “Žarko Zrenjanin” in Zrenjanin (n=85). The instrument for gathering data was the test which contained closed-ended questions. The data were presented in percentages. The obtained results show that students do not have a high level of knowledge in sociocultural contents which are related to geography, history, everyday life, customs, and famous persons in the area of art. Their knowledge is uneven, which is reflected in the fact that students have better knowledge in some segments from geography and everyday life, and in some segments they have less knowledge. On the basis of the conducted research, it can be concluded that it is necesary to work more on sociocultural competence of primary school students and to pay more attention to this not sufficiently studied area in Serbia.
Keywords: sociocultural competence; Spanish as a foreign language; primary school; test